2021
DOI: 10.1111/jace.18264
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and simulation of infrared emissivity properties of doped LaAlO3

Abstract: In this study, LaAlO 3 doped with Sr/Co/Mn was prepared by sol-gel method, with its infrared (IR) radiative properties and variation mechanism investigated by X-ray powder diffraction, X-ray photoelectron spectroscopy, IR, scanning electron microscopy. Meanwhile, the electronic band structure was simulated by Cambridge Serial Total Energy Package. The conclusions are as follows: the order of emissivity in the near-IR band is La 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…LaFeO 3 is widely used in catalysis, fuel cells, adsorption, and other fields due to its remarkable physical properties. In the orthorhombic unit cell of LaFeO 3 , the Fe 3+ ion lies at the center of the octahedron formed by six O 2– ions, while the La 3+ ion occupies the space between the FeO 6 octahedra. , Due to the limited adsorption capacity of pure LaFeO 3 for phosphate, it is an effective method to consider the substitution of La or Fe by cations with different valence states. Until now, several groups have reported Fe 3+ doping LaNiO 3 , Mn 2+ , Ce 3+ , and Cu 2+ doping LaAlO 3 , and Ca 2+ , Ti 4+ , Al 3+ , and Zn 2+ doping LaFeO 3 . All these studies have shown that doping with different cations can improve various properties of the perovskite, such as causing structural distortion, increasing the oxygen vacancy content, and even reducing the agglomeration and increasing the specific surface area. However, few studies have shown that doping perovskites can significantly improve the phosphate adsorption capacity .…”
Section: Introductionmentioning
confidence: 99%
“…LaFeO 3 is widely used in catalysis, fuel cells, adsorption, and other fields due to its remarkable physical properties. In the orthorhombic unit cell of LaFeO 3 , the Fe 3+ ion lies at the center of the octahedron formed by six O 2– ions, while the La 3+ ion occupies the space between the FeO 6 octahedra. , Due to the limited adsorption capacity of pure LaFeO 3 for phosphate, it is an effective method to consider the substitution of La or Fe by cations with different valence states. Until now, several groups have reported Fe 3+ doping LaNiO 3 , Mn 2+ , Ce 3+ , and Cu 2+ doping LaAlO 3 , and Ca 2+ , Ti 4+ , Al 3+ , and Zn 2+ doping LaFeO 3 . All these studies have shown that doping with different cations can improve various properties of the perovskite, such as causing structural distortion, increasing the oxygen vacancy content, and even reducing the agglomeration and increasing the specific surface area. However, few studies have shown that doping perovskites can significantly improve the phosphate adsorption capacity .…”
Section: Introductionmentioning
confidence: 99%